Entertaining a Great Earthquake in Western Nepal: Historic Inactivity and Geodetic Test for the Development of Strain - Bilham, Roger; Bodin, Paul; Jackson, Michael (Journal of Nepal Geological Society, 1995)
A 500-800 km long segment of the Himalaya bordered by the rupture zones of the great Bihar, 1934, and Kangra, 1905, earthquakes has not experienced a great earthquake for at least 200 years, and perhaps for as long as 750 years. The observed rate of occurrence of earthquakes is evidently too low to accommodate lndo/Tibetanslip which must therefore be accommodated by creep or occasional great earthquakes. Creep processes do not appear to be sufficiently fast, at least in central Nepal, where levelling data in the last two decades, and GPS data in the past 3 years, have been interpreted to account for at most 7 mm/year, or 30% of the inferred ≈20 mm/yr convergence signal. The measurement of 19th century geodetic networks in northern India, which have hitherto been neglected, potentially provides an estimate the rate of accumulation of elastic strain in W. Nepal. In view of the possibly disastrous consequences to the many tens of millions inhabitants of northern India and Nepal who would be affected by a great earthquake, an intense effort to explore further the historic record and the geographic limits of historic and future rupture is desirable.